Implementasi Manajemen Pendidikan Islam pada Lembaga Pendidikan di Era Globalisasi - Dedy Yansyah; Nasrudin Harahap; Nurul Hidayati Murtafiah (Journal on Education, 2023)
This examination expects to additionally comprehend how to fabricate the executives in the realm of schooling in the period of globalization, obviously, it should make an ideal Islamic instructive foundation with a cutting edge administration framework, then a training should be aware of the thoughts of the current administration and the desperation of its application. This kind of exploration utilizes subjective examination strategies. The information involved by the creators in this study is a wellspring of information that is significant and has likenesses with the conversation being considered. The strategy for gathering information in this study is Library Exploration (abstract review). The consequences of the review show that the utilization of the board in the administration of training in instructive establishments should be upheld by staff assets and different assets that are used to acknowledge high instructive authoritative execution to accomplish dependable quality alumni, assembling these faculty there is a component of giving inspiration, coordinating and driving so they function admirably and agreeably together. It should be finished to answer the difficulties of the times in the ongoing period of globalization.